Reversible local and global switching in multicomponent supramolecular networks: Controlled guest release and capture at the solution/solid interface - Lee, Shern Long (2015)
Dynamically switchable supramolecular systems offer exciting possibilities in building smart surfaces, the structure and thus the function of which can be controlled by using external stimuli. Here we demonstrate an elegant approach where the guest binding ability of a supramolecular surface can be controlled by inducing structural transitions in it. A physisorbed self-assembled network of a simple hydrogen bonding building block is used as a switching platform. We illustrate that the reversible transition between porous and nonporous networks can be accomplished using an electric field or applying a thermal stimulus. These transitions are used to achieve controlled guest release or capture at the solution–solid interface. The electric field and the temperature-mediated methods of guest release are operative at different length scales. While the former triggers the transition and thus guest release at the nanometer scale, the latter is effective over a much larger scale. The flexibility associated with physisorbed self-assembled networks renders this approach an attractive alternative to conventional switchable systems.